2021
DOI: 10.1001/jama.2021.13967
|View full text |Cite
|
Sign up to set email alerts
|

Change in Saliva RT-PCR Sensitivity Over the Course of SARS-CoV-2 Infection

Abstract: While real-time reverse transcriptase-polymerase chain reaction (RT-PCR) on nasopharyngeal swabs is the current standard for SARS-CoV-2 detection, saliva is an attractive alternative for diagnosis and screening due to ease of collection and minimal supply requirements. 1,2 Studies on the sensitivity of saliva-based SARS-CoV-2 molecular testing have shown considerable variability. 3 We conducted a prospective, longitudinal study to investigate the testing timeframe that optimizes saliva sensitivity for SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 5 publications
7
41
1
Order By: Relevance
“…In a study of ambulatory and symptomatic participants whose ages were more evenly distributed, NPS and MTS swabs were highly correlated with a mean of 7 days since onset of symptoms [20]. Congrave-Wilson et al, in agreement with the current study, found that saliva had the highest sensitivity in the first seven days post COVID-19 onset when using NPS as the reference [2]. Becker et al compared the sensitivity of saliva and NPS for detecting COVID-19 in a convalescent cohort 8-56 days since first symptom and found that NPS performed better [21].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In a study of ambulatory and symptomatic participants whose ages were more evenly distributed, NPS and MTS swabs were highly correlated with a mean of 7 days since onset of symptoms [20]. Congrave-Wilson et al, in agreement with the current study, found that saliva had the highest sensitivity in the first seven days post COVID-19 onset when using NPS as the reference [2]. Becker et al compared the sensitivity of saliva and NPS for detecting COVID-19 in a convalescent cohort 8-56 days since first symptom and found that NPS performed better [21].…”
Section: Discussionsupporting
confidence: 87%
“…Only one asymptomatic case was identified in our study so we could not compare the sensitivity of the two types of samples among asymptomatic COVID-19 cases. The evidence for using saliva to detect asymptomatic cases was mixed in previous studies [2,10] and further studies are needed to clarify this issue. In conclusion, the use of saliva is preferable for testing pre-symptomatic populations.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations